1990
DOI: 10.1128/mcb.10.7.3663
|View full text |Cite
|
Sign up to set email alerts
|

Activated T cells express a novel gene on chromosome 8 that is closely related to the murine ecotropic retroviral receptor.

Abstract: A novel cDNA clone (20.5) which is differentially expressed between two closely related T-lymphoma cell clones was isolated by subtraction-enriched differential screening. SL12.4 cells, from which the cDNA was isolated, have characteristics of thymocytes at an intermediate stage in development. A sister cell clone derived from the same tumor, SL12.3, does not express this mRNA, has a distinct phenotype, and expresses fewer genes required for mature T-cell function. The cDNA sequence predicts a highly hydrophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
78
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 49 publications
(28 reference statements)
6
78
0
Order By: Relevance
“…Expression of this gene is increased in T cells following treatment with conconavalin A (MacLeod et al 1990;Yoshimoto et al 1992) and in B cells after treatment with lipopolysaccharide (Yoshimoto et al 1992). Elevated expression is also a consequence of treatment with phorbol 12-myristate 13-acetate (PMA) or calcium ionophore (Yoshimoto et al 1992).…”
Section: Genes and Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Expression of this gene is increased in T cells following treatment with conconavalin A (MacLeod et al 1990;Yoshimoto et al 1992) and in B cells after treatment with lipopolysaccharide (Yoshimoto et al 1992). Elevated expression is also a consequence of treatment with phorbol 12-myristate 13-acetate (PMA) or calcium ionophore (Yoshimoto et al 1992).…”
Section: Genes and Developmentmentioning
confidence: 99%
“…Increased mCAT-1 expression has been linked to cell proliferation in a number of cases (MacLeod et al 1990;Yoshimoto et al 1992;Wu et al 1994). Expression of this gene is increased in T cells following treatment with conconavalin A (MacLeod et al 1990;Yoshimoto et al 1992) and in B cells after treatment with lipopolysaccharide (Yoshimoto et al 1992).…”
Section: Genes and Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, circumstantial evidence suggested that CD98hc was strongly linked to amino acid transport but was not the transporter itself (Bertran et al, 1992;Macleod et al, 1994). The ®rst light chain (Lc1 or LAT1) associated with CD98hc have been identi®ed at long last (Kanai et al, 1998, Mastroberardino et al, 1998Nakamura et al, 1999;Tsurudome et al, 1999), and this molecule proved to be TA1/E16 (Sang et al, 1995).…”
Section: Introductionmentioning
confidence: 99%